2021
DOI: 10.3390/ijms22158017
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Immune Signatures Indicative of Treatment Response and Immune-Related Adverse Events in Melanoma Patients under Immune Checkpoint Inhibitor Therapy

Abstract: To identify potential early biomarkers of treatment response and immune-related adverse events (irAE), a pilot immune monitoring study was performed in stage IV melanoma patients by flow cytometric analysis of peripheral blood mononuclear cells (PBMC). Overall, 17 patients were treated with either nivolumab or pembrolizumab alone, or with a combination of nivolumab and ipilimumab every three weeks. Of 15 patients for which complete response assessment was available, treatment responders (n = 10) as compared to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 42 publications
2
24
0
Order By: Relevance
“…The significance of monitoring the CD45RA+CD25+/CD4+ T cell ratio during anti-PD-1 therapy needs to be elucidated. On the other hand, a higher percentage of activated peripheral CD4+ T cells was detected in patients with irAEs before the second treatment cycle of ICIs 28 . The frequency of peripheral cytotoxic CD4+ T cells was shown to correlate with destructive thyroiditis induced by anti-PD-1 therapy 29 .…”
Section: Discussionmentioning
confidence: 90%
“…The significance of monitoring the CD45RA+CD25+/CD4+ T cell ratio during anti-PD-1 therapy needs to be elucidated. On the other hand, a higher percentage of activated peripheral CD4+ T cells was detected in patients with irAEs before the second treatment cycle of ICIs 28 . The frequency of peripheral cytotoxic CD4+ T cells was shown to correlate with destructive thyroiditis induced by anti-PD-1 therapy 29 .…”
Section: Discussionmentioning
confidence: 90%
“…However, we make reference to the fact that Reschke et al. used flow cytometry to examine peripheral blood samples from melanoma patients receiving ICIs and discovered that PD-1 downregulation had the greatest impact on CD3+, CD4+, and CD8+ T cells at all time points after treatment initiation and that CD8+CD38+ T cells and CD8+ effector memory T cells were higher at the time point of AEs ( 47 ). Kotwal et al.…”
Section: Discussionmentioning
confidence: 99%
“…events. and that CD8+CD38+ T cells and CD8+ effector memory T cells were higher at the time point of AEs(47). Kotwal et al compared 10 patients with ICIs-induced thyroiditis with healthy thyroid samples (n=5) by flow cytometry of thyroid fine needle aspirates and found a significant increase of CD8+ T lymphocytes in the thyroid gland of patients with ICIs-induced thyroiditis(48).…”
mentioning
confidence: 99%
“…One study has identified a decrease in TEM cell populations among patients who developed irAEs although only a significant drop among CD4 + TEM cells was observed [ 10 ]. Another group recently found that circulating TEM (both CD4 and CD8) trended down in patients that developed irAE, while the opposite was true in patients whose tumors responded to their therapy [ 11 ]. Additional work is needed to determine whether these disparate patterns represent mechanistic differences between the irAE developing in different organ systems, between different patient contexts, or an alternative explanation is responsible.…”
Section: Discussionmentioning
confidence: 99%